Crystallographic structural analysis in atom probe microscopy via 3D Hough transformation. - Yao, L; Moody, M; Cairney, J; Haley, D; Ceguerra, A; Zhu, C; Ringer, S (2011)
Whereas the atom probe is regarded almost exclusively as a technique for 3D chemical microanalysis of solids with the highest chemical and spatial resolution, we demonstrate that the technique can be used for detailed crystallographic determinations. We present a new method for the quantitative determination of crystal structure (plane spacings and angles) using a Hough transformation of the reconstructed atom probe data. The resolving power is shown to be high enough to identify poorly established, discontinuous planes that are typical in semiconducting materials. We demonstrate the determination of crystal geometry around a grain boundary and the use of the technique for the optimisation of tomographic reconstruction. We propose that this method will enable automatic spatial analysis and, ultimately, automated tomographic reconstruction in atom probe microscopy.